2006
DOI: 10.1212/01.wnl.0000242880.49051.1f
|View full text |Cite
|
Sign up to set email alerts
|

Distal myoclonus and late onset in a large Dutch family with myoclonus–dystonia

Abstract: We report a large myoclonus-dystonia (M-D) pedigree with a two-base pair deletion in Exon 5 of the epsilon-sarcoglycan gene. Three individuals had onset after age 40 years. Distal myoclonus of the arms was present in all 20 symptomatic mutation carriers. These findings expand the known phenotype of M-D and require revision of the current diagnostic criteria. Five of 14 asymptomatic mutation carriers who inherited the mutation from their mother showed minimal axial dystonia, arguing against a maternal imprintin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
1
1

Year Published

2007
2007
2013
2013

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 9 publications
1
27
1
1
Order By: Relevance
“…Our literature review identified 22 nonduplicated publications, which were classified as single‐family,7, 22, 23, 25, 28–32 multiple‐family,1–4, 9, 15, 20, 33 and larger‐scale studies with sequential probands or multiple unrelated cases26, 27, 34–36 (Supplementary Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Our literature review identified 22 nonduplicated publications, which were classified as single‐family,7, 22, 23, 25, 28–32 multiple‐family,1–4, 9, 15, 20, 33 and larger‐scale studies with sequential probands or multiple unrelated cases26, 27, 34–36 (Supplementary Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…This is in line with previous findings. However, patients with a typical M-D phenotype and a young-onset with a negative family history as well as patients with a typical M-D phenotype, late onset but a positive family history should also be considered for genetic testing, as mutation carriers with a late age of onset have been reported in a Dutch M-D pedigree 16. Possible M-D cases do not need to be tested for SGCE mutations.…”
Section: Discussionmentioning
confidence: 99%
“…MD is an autosomal dominant hereditary form of dystonia characterized by myoclonic jerks and dystonic postures or movements of the upper body. The condition usually becomes clinically manifest within the first two decades of life and is alcohol responsive (Foncke et al 2006; Gerrits et al 2006). In MD patients, the low-frequency drive had been reported at 3–7 Hz (Foncke et al 2007b).…”
Section: Introductionmentioning
confidence: 99%